"Who wants to join?" Visitors' willingness to participate in beach litter clean-ups in Nigeria. (June 2020) - Lucrezi, Serena; Digun-Aweto, Oghenetejiri
Abstract: Public involvement in beach litter clean-ups can help tackle marine litter while providing experiential learning, raising awareness and stimulating anti-litter behaviour. Beach visitors contribute to litter generation by inappropriate discarding behaviour, and engaging them in litter removal can be beneficial. This study assessed visitors' ( N  = 512) stated willingness to participate in litter clean-ups at Elegushi Royal Beach, Nigeria, which is under pressure from litter problems visitors contribute to, and potentially emblematic of organised litter clean-ups. Beach visitors recognised marine litter as a global and national problem but did not perceive the case study beach as being littered. Willingness to participate in beach litter clean-ups was marginal. However, it was positively correlated with previous participation in litter clean-ups, perceived collective responsibility and the importance of policy and investments in reducing litter. These results were used to propose a framework to engage and recruit visitors in beach litter removal campaigns. Highlights: Public involvement in beach litter clean-ups can be a positive management tool. Beach visitors contribute to litter problems but can also be a part of the solution. Visitors' willingness to partake in beach litter clean-ups was assessed in Nigeria. Willingness to participate was marginal but correlated with positive variables. A framework for visitors' engagement and recruitment was proposed.